Optimasi Biaya Pemenuhan Asupan Gizi pada Makanan bagi Anak-Anak Menggunakan Metode Simpleks Dua Fase - Pratomo Adinegoro; Rekyan Regasari Mardi Putri; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Children are part of a group of human age classification which are 0 - 12 years old. Fulfilling the nutrition requirement for the children is really important for their healthy life. One of the best way to fulfilling the nutrition requirement is by fulfilling the requirement of macronutrients. However, the ability of fulfilling the nutrition requirement is depending on how much they should spend their money on. Therefore, the optimization is needed to determine the best combination of food which can fulfil the nutrition requirement for the children and have a minimum cost. Simplex two-phase is one of optimization method from linear programming study. Simplex two-phase will minimize the cost to fulfil the nutrition requirement for the children. The outcome of this method calculation will be the quantity of food and the cost of it. The result show that the existence of feasible solution is determined by the selected foods and their cost which build the constraint function. Then, 0.1(or 1.5 gram) is the value of amount of food variable which has the minimum cost.